Evaluation of in-hospital management for febrile illness in Northern Tanzania before and after 2010 World Health Organization Guidelines for the treatment of malaria. - Andrew M Moon; Holly M Biggs; Matthew P Rubach; John A Crump; Venace P Maro; Wilbrod Saganda; Elizabeth A Reddy (PLoS ONE)
Objective In 2010, the World Health Organization (WHO) published updated guidelines emphasizing and expanding recommendations for a parasitological confirmation of malaria before treating with antimalarials. This study aimed to assess differences in historic (2007-2008) (cohort 1) and recent (2011-2012) (cohort 2) hospital cohorts in the diagnosis and treatment of febrile illness in a low malaria prevalence area of northern Tanzania. Materials and methods We analyzed data from two prospective cohort studies that enrolled febrile adolescents and adults aged ≥13 years. All patients received quality-controlled aerobic blood cultures and malaria smears. We compared patients' discharge diagnoses, treatments, and outcomes to assess changes in the treatment of malaria and bacterial infections. Results In total, 595 febrile inpatients were enrolled from two referral hospitals in Moshi, Tanzania. Laboratory-confirmed malaria was detected in 13 (3.2%) of 402 patients in cohort 1 and 1 (0.5%) of 193 patients in cohort 2 (p = 0.041). Antimalarials were prescribed to 201 (51.7%) of 389 smear-negative patients in cohort 1 and 97 (50.5%) of 192 smear-negative patients in cohort 2 (p = 0.794). Bacteremia was diagnosed from standard blood culture in 58 (14.5%) of 401 patients in cohort 1 compared to 18 (9.5%) of 190 patients in cohort 2 (p = 0.091). In cohort 1, 40 (69.0%) of 58 patients with a positive blood culture received antibacterials compared to 16 (88.9%) of 18 patients in cohort 2 (p = 0.094). In cohort 1, 43 (10.8%) of the 399 patients with known outcomes died during hospitalization compared with 12 (6.2%) deaths among 193 patients in cohort 2 (p = 0.073). Discussion In a setting of low malaria transmission, a high proportion of smear-negative patients were diagnosed with malaria and treated with antimalarials despite updated WHO guidelines on malaria treatment. Improved laboratory diagnostics for non-malaria febrile illness might help to curb this practice.